Pharmacological Screening of Viola odorata L. for Memory-Enhancing Effect via Modulation of Oxidative Stress and Inflammatory Biomarkers - Saleem, Uzma; Hira, Sundas; Anwar, Fareeha; Shah, Muhammad Ajmal; Bashir, Samia; Baty, Roua S.; Badr, Reem H.; Blundell, Renald; Batiha, Gaber El-Saber; Ahmad, Bashir (Frontiers in Pharmacology, 2021)
Purpose: Alzheimer disease (AD) is a progressive neurodegenerative disorder that is caused by neuroinflammation and oxidative stress. The present study aimed to characterize and then investigate the memory-enhancing potential of Viola odorata methanolic extract in lipopolysaccharide (LPS)–treated mice. Methods:V. odorata characterization was done by using the GCMS technique. Neuroinflammation was induced by the intracerebroventricular administration of LPS at a dose of 12 µg. Animals were divided randomly into six groups (n = 10). Group I was normal control, which was given vehicle. Group II was disease control, which received LPS (12 µg) via the intracerebroventricular route. Group III was standard, which was administered with donepezil (3 µg) orally for 21 days. Groups IV–VI were the treatment groups, which were administered with the extract at 100, 200, and 400 mg/kg dose levels orally respectively for 21 days. Groups III–VI received LPS (12 µg) on the first day along with their treatments. During the treatment, the animals were assessed for memory retention by employing different behavioral paradigms namely elevated plus maze, passive avoidance, foot shock and open field. Various mediators [endogenous antioxidants, neurotransmitters, and acetylcholinesterase (AChE)] involved in the pathogenesis of AD were quantified by using the UV spectrophotometric method. Results: Extract-treated groups showed a remarkable improvement in cognitive impairment in all behavioral paradigms. Oxidative stress biomarkers, that is, superoxide dismutase, catalase, and glutathione were raised dose-dependently in the treatment groups with a dose-dependent decrease in the malonaldehyde and AChE levels in the brains of the treated animals. The treatment groups showed decreased levels of inflammatory biomarkers, that is, tumor necrosis factor–alpha, nuclear factor kappa light-chain enhancer of activated β-cells, and cyclo-oxygenase, which supports the therapeutic effectiveness of the treatment. Conclusion: Based on behavioral, oxidative stress biomarker, and neuroinflammatory data, it is concluded that V. odorata possesses memory-enhancing activity and may prove a beneficial role in the management of AD.